Mid-Infrared High-Power InGaAsSb/AlGaInAsSb Multiple-Quantum-Well Laser Diodes Around 2.9 μm - Hongguang Yu; Chengao Yang; Yihang Chen; Jianmei Shi; Juntian Cao; Zhengqi Geng; Zhiyuan Wang; Haoran Wen; Enquan Zhang; Yu Zhang; Hao Tan; Donghai Wu; et al. (Nanomaterials)
Antimonide laser diodes, with their high performance above room temperature, exhibit significant potential for widespread applications in the mid-infrared spectral region. However, the laser’s performance significantly degrades as the emission wavelength increases, primarily due to severe quantum-well hole leakage and significant non-radiative recombination. In this paper, we put up an active region with a high valence band offset and excellent crystalline quality with high luminescence to improve the laser’s performance. The miscibility gap of the InGaAsSb alloy was systematically investigated by calculating the critical temperatures based on the delta lattice parameter model. As the calculation results show, In0.54Ga0.46As0.23Sb0.77, with a compressive strain of 1.74%, used as the quantum well, is out of the miscibility gap with no spinodal decomposition. The quantum wells exhibit high crystalline quality, as evidenced by distinct satellite peaks in XRD curves with a full width at half maximum (FWHM) of 56 arcseconds for the zeroth-order peak, a smooth surface with a root mean square (RMS) roughness of 0.19 nm, room-temperature photoluminescence with high luminous efficiency and narrow FHWM of 35 meV, and well-defined interfaces. These attributes effectively suppress non-radiative recombination, thereby enhancing internal quantum efficiency in the antimonide laser. Furthermore, a novel epitaxial laser structure was designed to acquire low optical absorption loss by decreasing the optical confinement factor in the cladding layer and implementing gradient doping in the p-type cladding layer. The continuous-wave output power of 310 mW was obtained at an injection current of 4.6 A and a heatsink temperature of 15 °C from a 1500 × 100 μm2 single emitter. The external quantum efficiency of 53% was calculated with a slope efficiency of 0.226 W/A considering both of the uncoated facets. More importantly, the lasing wavelength of our laser exhibited a significant blue shift from 3.4 μm to 2.9 μm, which agrees with our calculated results when modeling the interdiffusion process in a quantum well. Therefore, the interdiffusion process must be considered for proper design and epitaxy to achieve mid-infrared high-power and high-efficiency antimonide laser diodes.